BENEFITS OF ELECTRONIC HEALTH RECORDS IN HEALTH CARE DELIVERY SYSTEM IN NIGERIA (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This paper reported the benefits of electronic health records in health care delivery system in Nigeria. This article started with introduction, followed by discussion on health records management. Goals and benefits of electronic health records were brought to the bear and, applications used in implementing electronics health records, with their associated challenges in Nigeria were identified.The instrument used for data collection was validated questionnaire. A total of ninety six (96) copies of questionnaire were administered, eighty two (82) were found useful which represent 85.42% response rate. Retrieved data were analyzed data using descriptive statistics of frequency count, percentage distribution and mean.Findings revealed that accurate and complete information about a patient’s health is guaranteed with electronic health records for improved healthcare delivery system. Epileptic power supply, network issues and delay in data entries at the starting point were identified as challenges that constituted impediments against EHR implementation towards effective health care delivery system in NigeriaThe study concluded that effectiveness of health care delivery system depends on the extent to which electronic health records systems are taken seriously by health care professionals in various health institutions. Therefore, government at all levels are advised to give maximum support and required encouragement to the implementation of electronic health records systems, so as to ensure quality health care services in Nigeria